Resiliency enhancement of power system against intentional attacks - Farshad Faramarzi; Taher Niknam; Jamshid Aghaei; Mohammadrashid Rashidi (IET Renewable Power Generation, 2022)
Abstract Natural disasters, man‐made attacks, and cyber‐attacks are some of the main hazards of power system which can interrupt the process of continuous power delivery to the end users. In this way, man‐made attacks characteristics’ are fundamentally different from other hazards due to its adaptive strategy that allows attackers to target the most vulnerable parts of the power system. By choosing appropriate time and place; attackers always have advantages over the defender to penetrate the system and launch malicious actions. Therefore, it is quite necessary to take into account the optimal policy for allocating resources in the defender's strategy. This research proposes a four‐level Defence–Defence–Attack–Defence (DDAD) approach to improve the power system resilience against the intentional human attacks. A new defence level, a planning level, is added to the common three‐level Defence–Attack–Defence (DAD) model in power system planning state in order to prevent cut off loads and voltage drop beyond standard with lower cost. In the proposed method, load priority is used to classify the vulnerable sections. The proposed model is performed on IEEE‐30 bus test system and the results indicate the feasibility of the proposed method. As the results indicate, in proposed method less than 10% budget is needed compared with the previous method while all critical loads will be remained. Furthermore, the new method needs no security guard to protect transmission lines for 30 years.